2008
DOI: 10.1271/bbb.70833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Amino Acids on Methionine-Induced Hyperhomocysteinemia in Rats

Abstract: Rats were fed diets supplemented with 1% L-methionine with and without 2.5% various amino acids for 7 d to determine what amino acids other than glycine, serine, and cystine can suppress methionine-induced hyperhomocysteinemia. L-Glutamic acid, L-histidine, and L-arginine significantly suppressed methionineinduced enhancement of plasma homocysteine concentrations, but the mechanisms underlying the effect of these amino acids are thought not to be identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the present study, we did not test the effect of cystine, because the cystine content of casein is very low and cystine did not exhibit a hypohomocysteinemic effect when added to methionine-supplemented diets in rats (30). We recently reported that glutamic acid, histidine, and arginine significantly suppressed methionineinduced hyperhomocysteinemia when added to a methionine-supplemented diet at a level of 2.5%, although the effects of these amino acids were far weaker than those of glycine and serine (31). Hence, the possibility that some amino acids other than glycine and serine also contribute to the effect of moderate and high casein diets cannot be excluded.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, we did not test the effect of cystine, because the cystine content of casein is very low and cystine did not exhibit a hypohomocysteinemic effect when added to methionine-supplemented diets in rats (30). We recently reported that glutamic acid, histidine, and arginine significantly suppressed methionineinduced hyperhomocysteinemia when added to a methionine-supplemented diet at a level of 2.5%, although the effects of these amino acids were far weaker than those of glycine and serine (31). Hence, the possibility that some amino acids other than glycine and serine also contribute to the effect of moderate and high casein diets cannot be excluded.…”
Section: Discussionmentioning
confidence: 76%
“…The discrepancy between the results of the study by Verhoef et al (10) and the results of the present study appears to be due to different experimental conditions, e.g., single ingestion vs. successive feeding of diets. On the other hand, we recently reported that cysteine significantly increased plasma homocysteine concentration in rats when supplemented to a 25% caseinϩ1% methionine diet at a high (2.5%) level (13), suggesting that a combination of high levels of methionine and cysteine rather leads to an elevation of plasma homocysteine concentration. There are several explanations for the hypohomocysteinemic effect of NAC or cyst(e)ine.…”
Section: Discussionmentioning
confidence: 91%
“…Cystine was also added to both diets ( Table 1). The effect of cysteine on homocysteine is unclear because previous studies have reported that cysteine both increases (40,41) and decreases (42) homocysteine in human subjects. The higher concentrations of homocysteine may also be attributed to insulin resistance as it occurred in the offspring with higher HOMA-IR indices at weaning (Table 5) and at week 15 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Cystine was also added to both diets (Table 1). The effect of cysteine on homocysteine is unclear because previous studies have reported that cysteine both increases ( 40 , 41 ) and decreases ( 42 ) homocysteine in human subjects.…”
Section: Discussionmentioning
confidence: 98%